1)y/y^2-9 - 3/9-y^2 = y /y^2-9 - (-3/y^2-9) = y /y^2-9 + 3/y^2-9 = y+3/(y-3)(y+3)= 1/y-3
2)2x/x^2-4 - 4/4 - x^2 =2x/x^2-4 - (-4/x^2-4) = 2x+4/x^2-4 = 2(x+2)/(x-2)(x+2)= 2/x-2
3)x2/x-7 + 7x/7-x = x^2/x-7 - 7x/x-7 = x^2-7x/x-7 = x(x-7)/x-7= x
4)7/x^2-9x + 3x-7/x^2-9x =7+3x-7/x^2-9x= 3x/x^2-9x
5)5y-19/11y + 6y+8/11y =5y-19+6y+8/11y= 11y - 27/11y
6)y+3/y-3 - 9-y/y-3 =y+3-9-y/y-3=-3/y-3
7)12a+b/28a - b-30a/28a =12a+b-b-30a/28a = -28a/28a = -1
8)6a-4/2 - 2-3a/2 =6a-4-2-3a/2 = 3a+6/2 = 3(a+2)/2
9)b/a-b - a/a-b =-a/a-b - b/a-b = -(a-b)/a-b = -1
10)5a/a-b - 5b/a-b =5a-5b/a-b = 5(a-b)/a-b = 5
11)m^2/m-5 - 25/m-5 =m^2-25/m-5 = (m-5)(m+5)/m-5= m+5
12)a^2-47/a+7 - 2/a+7 =a^2-47-2/a+7 = a^2-49/a+7 = (a-7)(a+7)/a+7=a-7
13)m/m^2-n^2 - n/m^2-n^2 =m-n/m^2-n^2= m-n/(m-n)(m+n)=1/m+n
14)m2/m+n - n^2/m+n =m^2-n^2/m+n = (m-n)(m+n)/m+n = m-n
15)n^2/3n+3m - m^2/3n+3m =n^2-m^2/3n+3m = (n-m)(n+m)/3(n+m) = n-m/3
y=-x^4+8x^8-16,
y'=-4x^3+64x^7,
y'=0, -4x^3+64x^7=0,
4x^3(16x^4-1)=0,
x^3(4x^2+1)(4x^2-1)=0,
x^3(4x^2+1)(2x+1)(2x-1)=0,
x^3=0, x1=0,
4x^2+1=0, x^2=-1/4<0,
2x+1=0, x2=-1/2∉[0;3],
2x-1=0, x3=1/2;
x=0, y=-16,
x=1/2, y=-15 31/32,
x=3, y=6472.
max y = 6472,
min y = -16.